Shameless hags and tolerance whores: Feminist resistance and the affective circuits of online hate - Jenny Sundén; Susanna Paasonen (Taylor & Francis, 2025)
This article explores shamelessness as a feminist tactic of resistance to online misogyny, hate and shaming within a Nordic context. In our Swedish examples, this involves affective reclaiming of the term “hagga” (hag), which has come to embody shameless femininity and feminist solidarity, as well as the Facebook event “Skamlös utsläckning” (shameless extinction), which extends the solidarity or the hag to a collective of non-men. Our Finnish examples revolve around appropriating derisive terms used of women defending multiculturalism and countering the current rise of nationalist anti-immigration policy and activism across Web platforms, such as “kukkahattutäti” (aunt with a flower hat) and “suvakkihuora” (“overtly tolerant whore”). Drawing on Facebook posts, blogs and discussion forums, the article conceptualizes the affective dynamics and intersectional nature of online hate against women and other others. More specifically, we examine the dynamics of shaming and the possibilities of shamelessness as a feminist tactic of resistance. Since online humor often targets women, racial others and queers, the models of resistance that this article uncovers add a new stitch to its memetic logics. We propose that a networked politics of reclaiming is taking shape, one using collective imagination and wit to refuel feminist communities.